Kinetics of rifampicin and isoniazid administered alone and in combination to normal subjects and patients with liver disease. Issue 1 (January 1972) - Acocella, G.; Bonollo, L.; Garimoldi, M.; Mainardi, M.; Tenconi, L. T.; Nicolis, F. B.
Abstract : The possible existence of kinetic interactions between rifampicin and isoniazid and the effect of the concomitant presence of an impaired liver function were investigated in man. In a first study normal healthy subjects and patients with chronic liver disease received, on three different occasions, a single dose of 600 mg rifampicin or isoniazid and of rifampicin and isoniazid associated in randomized sequences. The results have shown that in both groups the serum levels, half-life values, and urinary excretion of each drug given alone are not significantly different from those observed when the other drug is associated. Serum levels and half-life of rifampicin and isoniazid were significantly higher in patients with chronically impaired liver. In a second study, rifampicin and isoniazid were given in combination at the same doses as in the first study over a period of one week. The results have shown a trend to decrease in the serum levels of rifampicin of the healthy subjects and a trend to increase in the patients with chronic liver disease on day 7 of treatment. In both groups a reduction in the half-life of rifampicin was also observed. No changes in serum isoniazid concentrations were observed between day 1 and day 7 in the healthy subjects, whereas a significant increase was observed in the patients. No significant changes in the half-life of isoniazid were observed.